2019
DOI: 10.1002/hed.25530
|View full text |Cite
|
Sign up to set email alerts
|

False negative rate of fine‐needle aspiration in thyroid nodules: impact of nodule size and ultrasound pattern

Abstract: Background To retrospectively evaluate the false negative rate of ultrasound‐guided fine needle aspiration (FNA) according to the nodule size and ultrasound pattern. Methods We included 432 consecutive thyroid nodules from 384 patients who underwent ultrasound‐guided FNA with benign results (≥1 cm). The false negative rate in the nodules was assessed according to the nodule size and ultrasound pattern based on the Korean‐Thyroid Imaging Reporting and Data System (K‐TIRADS). Results The overall false negative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…A meta-analysis reported that the estimated malignancy rate of nodules with benign cytological results was 3.7% in surgical specimens [ 185 ], and 1%–3.2% determined by repeat FNA or long-term follow-up [ 184 194 196 197 ]. Whether false-negative FNA rates are higher [ 86 198 199 200 ] or similar [ 85 201 202 203 ] for large nodules compared to small nodules is controversial. However, the false negative rates of FNA are relatively high (3.1%–18.2%) for high suspicion thyroid nodules [ 184 194 195 196 ].…”
Section: Us-based Management Of Thyroid Nodules After Fnamentioning
confidence: 99%
“…A meta-analysis reported that the estimated malignancy rate of nodules with benign cytological results was 3.7% in surgical specimens [ 185 ], and 1%–3.2% determined by repeat FNA or long-term follow-up [ 184 194 196 197 ]. Whether false-negative FNA rates are higher [ 86 198 199 200 ] or similar [ 85 201 202 203 ] for large nodules compared to small nodules is controversial. However, the false negative rates of FNA are relatively high (3.1%–18.2%) for high suspicion thyroid nodules [ 184 194 195 196 ].…”
Section: Us-based Management Of Thyroid Nodules After Fnamentioning
confidence: 99%
“…In some studies, it has been shown that nodule ultrasound patterns can also affect the number of false-negative results (14), so at the present study, only solid nodules were subjected to FNA. In a study conducted by Cappelli et al, sampling was only done using complex nodules (10).…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies have evaluated Korean TIRAD (K-TIRAD) scores in association with false negatives and found that nodules >3 cm with a K-TIRAD 4 (intermediate suspicion of malignancy) lesion or greater were associated with a higher rate of false negatives. 6,8 Similarly, in nodules >4 cm with suspicious US patterns, the false-negative rate was 42.5% and lobectomy was recommended in these patients. 7 Current ATA guidelines for surveillance of thyroid nodules with benign FNAs recommend repeat biopsy at 1 year only for nodules with high suspicion ultrasound pattern.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 There are conflicting results regarding which factors impact false-negative rate including nodule size, multi-nodularity, microcarcinomas, and expert cytopathologist involvement. [4][5][6] Current American Thyroid Association (ATA) guidelines for surveillance of nodules that have had a benign FNA are based on sonographic appearance of the nodule but without correlation to TI-RADS scoring or size. 7 Indeed, few studies have investigated the relationship between ultrasound risk stratification systems and false-negative FNAs of thyroid nodules.…”
Section: Introductionmentioning
confidence: 99%